(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Arthritis and inflammation are prevalent health issues that significantly impact the quality of life. With the limitations and side effects associated with conventional treatments, there is a growing interest in natural remedies. Cymbidium species, a genus of orchids widely used in traditional medicine, have shown potential anti-arthritic and anti-inflammatory properties. This review aims to compile and evaluate the existing research on the therapeutic effects of Cymbidium species on arthritis and inflammation. This review aims to provide a comprehensive analysis of the anti-arthritic and anti-inflammatory activities of Cymbidium species, focusing on their phytochemical constituents, mechanisms of action, and potential as natural therapeutic agents. Cymbidium species exhibit significant anti-arthritic and anti-inflammatory activities, supported by both in vitro and in vivo studies. The bioactive compounds in these plants, particularly flavonoids and tannins, play a crucial role in their therapeutic effects. While the current findings are promising, further research, including well-designed clinical trials, is needed to confirm the efficacy and safety of Cymbidium species in human populations. This review underscores the potential of Cymbidium species as a valuable source of natural remedies for managing arthritis and inflammation, encouraging further exploration in this field.